Posted by **jasmine20** on Thursday, February 8, 2007 at 11:39pm.

rewrite the equation 2x-3y= -6 as a function of x.

My answer.

f (x) = (2)/(3) x + 2

No.

2x=3y - 6

divide by two.

x=3/2 y -2

hold on i was looking it over. wouldn't it be:

2x-3y=-6

would actually be:

-3y=-2x-6

y= 2/3x+2

because you said that it would be x=3/2y-2

but how can that be?

## Answer this Question

## Related Questions

- math,correction,algebra - is this correct: rewrite the equation 4x-10y = 11 as a...
- algebra 116 - Rewrite the equation y = 5x – 2 as a function of x. This problem ...
- math - Rewrite the equation 4x – 6y = –30 as a function of x. Subtract 4x from ...
- math - rewrite each equation as afunction of x.-3y+4y=11 Where are the equations...
- Math - How would you rewrite the equation y = 3x+1 as a function of x. Hmmm. It ...
- pre-algebra - Rewrite the equation so the variable is alone. Solve to find the ...
- math,correction,plz - Evaluate (15-5)/[((12)/(2*2))-2] my answer that i keep ...
- Math - The graph of a quadratic function has vertex(3,-4) and passes through the...
- Math - The graph of a quadratic function has vertex(3,-4) and passes through the...
- Math - Compute the maximum product for two positive numbers x and y with the ...